2017
DOI: 10.1002/col.22155
|View full text |Cite
|
Sign up to set email alerts
|

The “C test” for tritan discrimination

Abstract: The aim of this study was to develop and evaluate a clinical standard capable of generating ordinal measures of monocular tritan discrimination. A novel pseudoisochromatic plate test was developed, called the "C test." It contains 10 progressively desaturated plates arranged in perceptually distinct steps that provide a standard for analyzing the threshold for tritan discrimination. The most difficult plate that can be detected is the "C score." Relevant diagnostic findings including the C score, Logmar acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…During a 4 month period all patients presenting to an adult ophthalmology clinic had their routine clinical findings (including logmar acuity and a C test score) recorded in an Excel spreadsheet as part of a study to establish normative results for the C test. The results obtained from the first 243 observers were published [8] then a further 149 subjects were assessed in an attempt to establish normal scores for eyes with NC > 4. During the test evaluation process I observed that amblyopic eyes had high C test scores, despite poor logmar acuity, and this incidental observation prompted the current analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During a 4 month period all patients presenting to an adult ophthalmology clinic had their routine clinical findings (including logmar acuity and a C test score) recorded in an Excel spreadsheet as part of a study to establish normative results for the C test. The results obtained from the first 243 observers were published [8] then a further 149 subjects were assessed in an attempt to establish normal scores for eyes with NC > 4. During the test evaluation process I observed that amblyopic eyes had high C test scores, despite poor logmar acuity, and this incidental observation prompted the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The C test for tritan discrimination is a novel plate test that provides an ordinal score from 1 to 10, corresponding to the perception of sequentially decreasing amounts of tritan contrast [8]. Because tritan contrast decreases with increasing grades of nuclear sclerosis, plate tests for tritan contrast require stronger daylight illumination than red/green plate tests in older observers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation